2015
DOI: 10.1007/s11164-015-2108-0
|View full text |Cite|
|
Sign up to set email alerts
|

Insecticidal effect of Mentha pulegium L. and Mentha suaveolens Ehrh. hydrosols against a pest of citrus, Toxoptera aurantii (Aphididae)

Abstract: Essential oils proved their efficiency as natural insecticides to fight many pests of stored products and crops whereas the hydrosols have not been evaluated yet. The objective of this work is to assess the insecticidal effect of hydrosols extracted from Mentha suaveolens Ehrh. and Mentha pulegium L. toward an insect pest of citrus, Toxoptera aurantii (Homoptera, Aphididae). The extraction of hydrosols was carried out by hydro-distillation using Clevenger apparatus and then the chemical composition was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…suaveolens and M . pulegium , respectively) (Zekri et al., ). The hydrosols caused adverse effects on the fecundity of both pests, too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suaveolens and M . pulegium , respectively) (Zekri et al., ). The hydrosols caused adverse effects on the fecundity of both pests, too.…”
Section: Discussionmentioning
confidence: 99%
“…Petrakis, Kimbaris, Lykouressis, Polissiou, and Perdikis (2015) showed that hydrosols had a repellent effect, but their toxicity was very low against the peach aphid Myzus persicae (Sulzer) (Hemiptera: Aphididae). Zekri, Handaq, El Caidi, Zair, and El Belghiti (2016) reported on the insecticidal activity of the compounds of the hydrosols from Mentha species against the citrus aphid Toxoptera aurantii Boyer (Hemiptera: Aphididae). The above promising results of hydrosols in pest control indicate their potential to be used as insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that essential oils of spearmint were efective against Lycoriella ingenua at 20 × 10 −3 mg/mL [10]; fumigation allowed controlling all stages of Callosobruchus maculatus; and the egg stage was the most susceptible stage [163]. Also, compared to M. pulegium, a M. suaveolens hydrosol showed higher insecticidal activity toward an insect pest of citrus, Toxoptera aurantii [164].…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…Other compositions have been also reported as cis ‐piperitol and 1,8‐cineol chemotypes . This subspecies has the major economic interest because of its pharmacological and insecticidal properties . Besides, the piperitenone oxide is useful as starting point for heterocycle synthesis …”
Section: Introductionmentioning
confidence: 99%
“…[5] This subspecies has the major economic interest because of its pharmacological and insecticidal properties. [3][13] [15] Besides, the piperitenone oxide is useful as starting point for heterocycle synthesis. [16] Concerning insularis and timija subsp., their EO composition has also widely reported, showing a great chemical variability.…”
Section: Introductionmentioning
confidence: 99%